THE PREVALENCE OF HEALTH FACILITY DELIVERIES AMONG WOMEN OF REPRODUCTIVE AGE IN THE CATCHMENT AREAS OF KALISIZO HOSPITAL,KYOTERA DISTRICT. - Nyangoma, Jackline (Student’s Journal of Health Research Africa, 2023)
Background This study aims to document the prevalence of health facility deliveries among women of reproductive age in the catchment areas of Kalisizo Hospital, Kyotera district. Health Facility delivery refers to birth that occurs inside a health facility whether private or government. Mothers who had previously given birth at home were 40 times more likely to give birth at home again than those who previously gave birth at a health facility and this is associated with many more maternal deaths and normally end up undocumented. Hence there is a need to increase the prevalence of health facility delivery if the SDG target of reducing maternal mortality is to be achieved. Therefore, this study seeks to assess the prevalence of health facility deliveries among mothers living in the catchment areas of Kalisizo Hospital, Kyotera district, Uganda. Methodology A cross-sectional, mixed methods approach is used to better understand the prevalence of health facility deliveries among women of reproductive age in the catchment areas of Kalisizo Hospital, Kyotera district. Results The prevalence of health facility deliveries among mothers in the catchment areas of Kalisizo Hospital in Kyotera district was 89.7% (95% CI:88.7-90.6) and 10.3% for non-health facility deliveries (95% CI:9.4-11.1). Conclusion Mother’s attendance of ANC during pregnancy, marital status, and mother’s gravidity/parity, availability of skilled birth attendants, MCH visits by community health workers, the experience of complications during and after labor, setoff time during labor to the delivery place were significant determinants of health facility deliveries. Recommendation Programs promoting health facility births in similar settings should prioritize boosting ANC attendance, MCH visits by community health workers, improving the experiences of mothers at maternal and antenatal wards, and training health workers to manage emergencies to improve the outcome of delivery.